Social Cohesion and Firms' Access to Finance in Africa - Yabibal M. Walle (Social Indicators Research, 2023)
Social cohesion has recently gained increasing attention in academic and policy circles. Apart from being a necessary feature of stable societies per se, social cohesion is also a key factor for sustainable economic development. One potential means through which social cohesion could foster economic development is by enhancing financial development. In this paper, I examine whether social cohesion is significantly associated with firms' access to finance in Africa. To this end, I use a recently constructed dataset on social cohesion in Africa, which contains indices for the three pillars of social cohesion – trust, inclusive identity and cooperation for the common good. Combining this dataset with that of the World Bank Enterprise Surveys, I build a sample which covers more than 12,600 firms and 27 African countries. The results show that all three components of social cohesion are positively associated with at least one measure of firms' access to external finance. In particular, trust – but not inclusive identity and cooperation for the common good – is significantly associated with the likelihood that firms have a checking or savings account, or are financially constrained. When we measure access to finance with respect to having a line of credit or a loan from a financial institution, all the three pillars of social cohesion, including inclusive identity and cooperation for the common good, are related to access to finance. The results are robust to addressing endogeneity concerns using a heteroskedasticity-based identification strategy.
Keywords: G21; O16; O43; O55; Z13; 300; Access to finance; Social cohesion; Trust; Cooperation for the common good; Identity; Africa